A Simple Design of UWB Small Microstrip Slot Antenna with Band-Notched Performance by using a T-Shaped Slit and a Pair of UShaped Conductor-Backed Plane - Ojaroudi, Mohammad; Ojaroudi , Nasser; Ghadimi, Noradin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a simple and compact ultra wideband printed slot antenna with bandnotch performance is designed and manufactured. In order to increase the impedance bandwidth of the square slot antenna, we use two U-shaped parasitic structures inside the rectangular slot on the ground plane that with this structure UWB frequency range can be achieved. Additionally, by using a T-shaped slit on the ground plane, a frequency notched band performance has been obtained. The designed antenna has a small size of 20×20 mm while showing the radiation performance in the frequency band of 3.05 GHz to over 12 GHz with a band rejection performance in the frequency band of 5.1 GHz to 6.05 GHz